Administrative Courts as Advocates for Non-Discriminatory Competence Behaviors in Poland – LGBTQ+ Case - Firlus, Jakub Grzegorz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The study addresses the issue of the relationship between the attitude of the courts and the protection of LGBTQ+ rights. The author is of the opinion that formalism can to a greater extent contribute to the promotion of non-discrimination among administrative bodies. The empirical material for the study was the cases of anti-LGBT resolutions and the issue of associative discrimination of a child whose parents are persons of the same sex. The role of the advocate of the non-discriminatory attitudes is the first step on the way to building an inclusive and tolerant legal environment.